Alterations of iron homeostasis as a potential druggable driver of long COVID - Marques, Oriana; Muckenthaler, Martina (Nature immunology, 2024)
Drivers of persistent symptoms after acute COVID-19 remain largely unknown. Alterations in immune function, iron homeostasis and dysregulated erythropoiesis are described as treatable correlates of post-acute sequelae of COVID-19.
Gesehen am 15.08.2024